1985
DOI: 10.3171/jns.1985.62.4.0513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of treatment of normal-pressure hydrocephalus

Abstract: Ten patients with dementia due to normal-pressure hydrocephalus were evaluated prospectively according to a planned, longitudinal protocol for 4 to 12 months. Information recorded at each visit included clinical history, medical and neurological examination, psychometric scoring by Mini-Mental Status Questionnaire, measurement of ventricular size and local cerebral blood flow, and partition coefficients (local lambda changes) (1 lambda) by xenon contrast computerized tomography scanning. Cerebrospinal fluid sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 36 publications
1
21
1
1
Order By: Relevance
“…9). Earlier studies on ischemic sites in iNPH before surgery 16,17,19,20,22,24,[26][27][28][29][30][31][32]34) have reported various patterns of these two pathophysiological conditions according to the disease stage of iNPH. While one group reports only reductions in hypoperfusion, 34) most authors agree that the CBF improves after surgery in shunt-effective cases, in light of the compensatory increase of the blood flow at normoperfusion sites in non-improved hypoperfusion cases after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9). Earlier studies on ischemic sites in iNPH before surgery 16,17,19,20,22,24,[26][27][28][29][30][31][32]34) have reported various patterns of these two pathophysiological conditions according to the disease stage of iNPH. While one group reports only reductions in hypoperfusion, 34) most authors agree that the CBF improves after surgery in shunt-effective cases, in light of the compensatory increase of the blood flow at normoperfusion sites in non-improved hypoperfusion cases after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…9,[12][13][14][17][18][19][20][21][22]24,[26][27][28][29]31,32,34) The results from reports on preoperative ischemic sites and postoperative sites of increased blood flow have varied, 13,17,19,20,22,24,26,27,31,32) however, and no firm consensus has been reached. In this study we use N-isopropyl-( 123 I)-P-iodoamphetamine single photon emission computed tomography ( 123 I-IMP SPECT) to compare the CBF and perfusion patterns of the cerebral cortex assessed by the three-dimensional stereotactic surface projection (3D-SSP) Z-score images at each site before and after surgery in iNPH cases effectively resolved by shunt intervention (shunt-effective cases).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are supported by other studies. 57,70,74,76,117,128) A PET study reported the mean CBF decreased in the cerebrum and cerebellum with regional decrease in the basal ganglia and thalamus but not in the white matter. 82) There are few studies supporting the correlation between reduced flow and degree of symptoms.…”
Section: Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
“…54B) The involvement of autoregulatory impairment is still controversial. 70,74,82,118) Thus, CBF measurements can show diffuse or regional decrease of CBF in NPH, but they are insufficient for the definite diagnosis of iNPH and also insufficient for the indication of shunt surgery (Recommendation grade C). However, CBF studies are useful in differentiating iNPH from other disorders of dementia, including Alzheimer's disease.…”
Section: Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
See 1 more Smart Citation